Technology and foreign language learning: student perceptions on the feasibility of using WBI (Web-Based Instruction) to supplement the on-campus foreign language courses in UiTM / Goh Ying Soon ... [et al.] - Goh, Ying Soon; Ng, Ah Suan; Raja Bani Amin, Raja Mariam; Wan Mamat, Wan Anuar (2004)
This study seeks to identify the factors influencing the use of WBI to supplement the on-campus foreign language courses in UiTM, to assist the researcher to discover the problems faced and to suggest some possible ways to utilize technology in enhancing foreign language learning. In seeking greater understanding, this research is a qualitative study using purposive sampling technique of Bumiputera students who were taking Mandarin, French and Arabic courses in UiTM Dungun Campus as its main source of information. Taken as a whole the findings confirm that students do have an unenthusiastic perception of the feasibility of using WBI (Web-Based Instruction) to supplement the on-campus foreign language courses in UiTM, Terengganu Branch. Nevertheless, the findings show more affirmative viewpoints are found among French and Arabic learners. In order to employ WBI in supplementing the on-campus foreign language courses, auxiliary and in-depth discussion and scrutiny have to be made.